SOCIAL PROBLEMS AND ENVIRONMENT - Kant, Mani; Shouche, Shobha (International Journal of Research -GRANTHAALAYAH, 2015)
Without self-understanding we cannot hope for Enduring solutions to environmental problems, Which are fundamentally human problems. —Yi-Fu Tuan, 1974 Human beings interact both with the social world and nature. Both, economic development and stable environment are required for the continual improvement of lifestyle and living standards of the people in the society and for the Earth Community as a whole. But until now, the development was human oriented and limited to rich nations. The development was achieved by damaging the environment and over exploitation of natural resources which were nonrenewable. That caused instability of environment and crossed the threshold limit of environmental damage. The major challenge of our times is to find new and practical ways of drawing inspiration from the rich diversity of human experience as well as modern scientific insights in order to establish effective means of governing human behavior to ensure that we contribute to the prosperity of the whole Earth Community instead of destroying it.